The Effect of Product Innovation and Lifestyle on Purchasing Decisions for Bardi Smart home Brand Products on Tokopedia - Aureria, Catherine; Ihdina Gustina, S.E., M.M (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
One of the e-commerce sites used for buying and selling in Indonesia is Tokopedia. This platform makes it simple to connect customers and merchants. Among the smart home companies that have joined Tokopedia since 2019 is Bardi Smart Home. This Bardi product is made in Indonesia and offers high-quality smart home goods. The purpose of this study is to ascertain how lifestyle and product innovation affect consumers' decisions to buy Bardi Smart Home brand products on Tokopedia. The population of this study, which employs a quantitative methodology, consists of all consumers who have rated the Bardi Official Store on the Tokopedia app. The Hair et al. formula was used to obtain the sample, yielding 120 responses. A questionnaire with a Likert scale was employed as the research tool. The findings demonstrated that lifestyle and product innovation significantly and favorably influence consumer choices.